2021
DOI: 10.3390/molecules26020371
|View full text |Cite
|
Sign up to set email alerts
|

Melanogenesis Promoting Effect, Antioxidant Activity, and UPLC-ESI-HRMS Characterization of Phenolic Compounds of Argan Leaves Extract

Abstract: The use of natural products for the regulation of skin pigmentation is gaining popularity. In the present study, we evaluated the effect of argan leaves extract (ALE) on melanogenesis in B16 melanoma cells, determined its antioxidant activity, then quantified and identified its phenolic components. B16 cells were treated with various concentrations of ALE, then the cell viability and proliferation were assessed using MTT assay while the melanin content was determined using spectrophotometric methods. The expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…By inhibiting the overproduction and accumulation of melanin in the skin that cause numerous related pigment disorders like melasma, freckles or lentigines, dermatitis, and geriatric skin pigmentation [ 14 ], APC may become an alternative natural and noncytotoxic therapeutic agent against hyperpigmentation disorders. It also has a potential use in cosmetics like argan oil [ 51 ] and other argan oil extraction by-products, argan fruit shells [ 52 ], argan leaves [ 53 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…By inhibiting the overproduction and accumulation of melanin in the skin that cause numerous related pigment disorders like melasma, freckles or lentigines, dermatitis, and geriatric skin pigmentation [ 14 ], APC may become an alternative natural and noncytotoxic therapeutic agent against hyperpigmentation disorders. It also has a potential use in cosmetics like argan oil [ 51 ] and other argan oil extraction by-products, argan fruit shells [ 52 ], argan leaves [ 53 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that argan oil and argan press cake have melanin synthesis inhibitory effects [ 17 , 20 ], whereas extracts of other parts of the argan tree such as argan fruit shell and leaves promote melanogenesis [ 18 , 19 ]. These findings show that the different parts of argan plants are rich sources of materials for melanogenesis regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other parts of the argan tree and fruit also have melanogenesis regulatory effect. Argan fruit shell promotes melanogenesis by activating the cAMP pathway [ 18 ], an extract of argan leaves also promotes melanogenesis [ 19 ], whereas the press cake from argan oil extraction process downregulates MITF and inhibits melanogenesis [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, L-dopaquinone can also be converted to L-dopachrome, and TRP-2 can isomerize dopachrome to 5,6-dihydroxyindole-2-carboxylic acid (DHICA); TRP-1 then oxidizes DHICA to indole-5,6-quinone-2-carboxylic acid, which is eventually converted to eumelanin. [6][7][8][9] Thus, modulating the activity of enzyme cascades consisting of several key enzymes, such as TRY, TRP-1, and TRP-2, is considered an important strategy in the development of skin pigmentation treatments. 10,11 Microphthalmia-associated transcription factor (MITF) is involved in the survival, proliferation, and differentiation of melanocytes and is an important transcriptional regulator of TRY, TRP-1, and TRP-2.…”
Section: Introductionmentioning
confidence: 99%